Recent Amendments To The Egyptian Family Law - Ibrahim, Ahmad; Abu Bakar, Abdullah (Journal of Malaysian and Comparative Law, 2018)
A new law, Law No. 44 of 1979, has been enacted in Egypt to make amendments to the existing family law. The new law has amended the earlier laws, Law No. 15 of 1920 and Law No. 25 of 1929. The translation of the former laws (as amended by the new law) is given in the Appendix.